2019
DOI: 10.1371/journal.pone.0215535
|View full text |Cite
|
Sign up to set email alerts
|

Novel mouse monoclonal antibodies specifically recognizing β-(1→3)-D-glucan antigen

Abstract: β-(1→3)-D-Glucan is an essential component of the fungal cell wall. Mouse monoclonal antibodies (mAbs) against synthetic nona-β-(1→3)-D-glucoside conjugated with bovine serum albumin (BSA) were generated using hybridoma technology. The affinity constants of two selected mAbs, 3G11 and 5H5, measured by a surface plasmon resonance biosensor assay using biotinylated nona-β-(1→3)-D-glucan as the ligand, were approximately 11 nM and 1.9 nM, respectively. The glycoarray, which included a series of synthetic oligosac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 39 publications
1
36
0
1
Order By: Relevance
“…In addition, protective efficacy in mice vaccinated with a single injection followed by a lethal dose to C. albicans infection was obtained. In this case, a higher survival rate was observed in mice receiving mAb 5H5, which has high affinity and specificity as an IgG3, capable of inducing antibody-dependent cytotoxicity and cell phagocytosis more effectively than IgG1, being able to target mother cells, the main infective propagules [4].…”
Section: Candida Sppmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, protective efficacy in mice vaccinated with a single injection followed by a lethal dose to C. albicans infection was obtained. In this case, a higher survival rate was observed in mice receiving mAb 5H5, which has high affinity and specificity as an IgG3, capable of inducing antibody-dependent cytotoxicity and cell phagocytosis more effectively than IgG1, being able to target mother cells, the main infective propagules [4].…”
Section: Candida Sppmentioning
confidence: 89%
“…The increased numbers of immunocompromised hosts, global travel, climate alterations, and the common use of invasive devices have resulted in significant increases in rates of invasive mycoses. The medical mycology community has responded to this crisis by seeking out new approaches to combat these diseases, including through the development of vaccines and monoclonal antibodies (mAbs) [1][2][3][4][5] Recent studies show that systemic mycoses are a leading cause of morbidity and mortality in the US, being responsible for the deaths of more than 1.6 million people [2,6] with annual costs over $7.2 billion dollars [7][8][9]. There is, however, a significantly poorer awareness of the global incidence of systemic mycoses reinforced by the typical lack of transmissibility of fungal diseases [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a mouse-human chimera and a scFv-Fc derived from 2G8 were shown to promote killing of C. albicans by isolated neutrophils and to protect mice in a vulvovaginal model of infection [31]. In 2019, Matveev et al reported that an IgG 1 specific for β-1,3-glucan delayed germination of A. fumigatus conidia and improved survival of mice infected with C. albicans via the intravenous route [32].…”
Section: Protective Antibodies Against Candida Albicansmentioning
confidence: 99%
“…␤-Glucan is composed of D-glucose units linked by ␤-1,3glycosidic bonds (␤-1,3-D-glucan), which is the most common ␤-glucan structure produced by plants (␤-1,3-/␤-1,4-glucan) (1), bacteria (␤-1,3-glucan) (2), fungi (3), and algae (4) (␤-1,6-/ ␤-1,3-glucan); of interest, ␤-1,3-D-glucan has been at the mainstream of glucan research. In addition, ␤-1,3-D-glucan-specific recognition proteins such as the limulus coagulation factor G in horseshoe crab (5), ␤-1,3-glucan recognition protein in insects (6), dectin-1 (7), and immunoglobulin (8,9) in mammals are discovered in a wide range of species and applied to ␤-1,3-Dglucan-specific detection systems (10 -13). Among these, the most commonly used in the world is factor G from horseshoe crab, a highly-sensitive and rapid assay.…”
mentioning
confidence: 99%